The Influence Of Social Play On The Formation Of Social Caring Character In The Children Group B5 In Tk Vita Sejahtera Palembang - gumay, nadia aisya (Indonesian Journal of Islamic Early Childhood Education, 2018)
Pre Experimental Research with one-shot case study design entitled The Influence of Social Playing on the Character Building for Child Care B5 group in Tk Vita Sejahtera Palembang, has a goal to know the effect of social play on the formation of social care character the sampling technique used is purposive sampling with reason for social care of children who are still low in class B5. Sample amounted to 26 children consisting of 18 boys and 8 grils The treatment was done as each treatment was observed with observation got the score and converted into value into 4 categories. From 4 meetings in get the average value =  77,11 and S = 16,6 used to calculate Test t From the results of data analysis Test t obtained = 4,46   value  = 1,71  with significant 5% and dk (25) in accordance with the criteria testing tausr ta In conclusion there is the influence of social play on the formation of social care character of children in the group B5 Tk Vita Sejahtera Palembang. It can be proven that social care as many as 13 children (50% with BSB category, 8 children (30%) with BSH category, and 4 children (15%) in MB category as much as 1 child 3%) included in BB category. Out of the four predominantly indicator Meetings are indicators having a sense of responsibility, giving assistance, and socializing to others, while indicators that have not yet emerged are showing empathy. Seeing the results obtained is advisable for the next researcher to conduct the same research with emphasis on indicators showing empathy.